A mouse model for embryonal tumors with multilayered rosettes uncovers the therapeutic potential of Sonic-Hedgehog inhibitors - Neumann, Julia; Wefers, Annika K.; Korshunov, Andrey; Chavez, Lukas; Kool, Marcel (Nature medicine, 2017)
Embryonal tumors with multilayered rosettes (ETMRs) have recently been described as a new entity of rare pediatric brain tumors with a fatal outcome. We show here that ETMRs are characterized by a parallel activation of Shh and Wnt signaling. Co-activation of these pathways in mouse neural precursors is sufficient to induce ETMR-like tumors in vivo that resemble their human counterparts on the basis of histology and global gene-expression analyses, and that point to apical radial glia cells as the possible tumor cell of origin. Overexpression of LIN28A, which is a hallmark of human ETMRs, augments Sonic-hedgehog (Shh) and Wnt signaling in these precursor cells through the downregulation of let7-miRNA, and LIN28A/let7a interaction with the Shh pathway was detected at the level of Gli mRNA. Finally, human ETMR cells that were transplanted into immunocompromised host mice were responsive to the SHH inhibitor arsenic trioxide (ATO). Our work provides a novel mouse model in which to study this tumor type, demonstrates the driving role of Wnt and Shh activation in the growth of ETMRs and proposes downstream inhibition of Shh signaling as a therapeutic option for patients with ETMRs.